2023
DOI: 10.1039/d2cp05120f
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational insights into luminescence in atomically precise bimetallic Au6−nCun(MPA)5 (n = 0–2) clusters

Abstract: Bimetallic nanoclusters (NCs) have emerged as a new class of luminescent materials for potential applications in sensing, bio-imaging, and light-emitting diodes (LEDs). Here, we have synthesized copper-gold bimetallic nanoclusters (AuCu...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…We have synthesized Au 6 NCs, Cu 6 NCs, and Au 4 Cu 2 NCs utilizing a one-pot synthesis method in an aqueous medium with MPA as a capping ligand. 56 The TEM images of as-prepared Cu 6 NCs and Au 6 NCs depict the formation of ultrasmall nanoclusters with spherical morphology and an acquired particle size distribution indicating a size of nearly 2 nm (Fig. S1 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have synthesized Au 6 NCs, Cu 6 NCs, and Au 4 Cu 2 NCs utilizing a one-pot synthesis method in an aqueous medium with MPA as a capping ligand. 56 The TEM images of as-prepared Cu 6 NCs and Au 6 NCs depict the formation of ultrasmall nanoclusters with spherical morphology and an acquired particle size distribution indicating a size of nearly 2 nm (Fig. S1 †).…”
Section: Resultsmentioning
confidence: 99%
“…The Cu 6 NCs are non-luminescent while Au 6 NCs exhibit an emission peak at 520 nm which is red-shifted to 620 nm in the case of Au 4 Cu 2 NCs, due to the tunability of the HOMO–LUMO gap after the inclusion of Cu atoms in Au NCs. 56 Moreover, the recorded excitation spectra of as-prepared NCs can be seen in Fig. S6 †.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand-protected metal nanoclusters (MNCs) with less number of metal atoms having core diameters <2 nm are recognized as a new class of materials for their unique physicochemical properties, which are widely different from single metal atoms and larger-sized metal nanoparticles. These metal NCs exhibit many interesting properties including discrete HOMO–LUMO band gap, tunable photoluminescence (PL), large Stokes shift, and core–shell-type structures. , PL is one of the most fascinating properties of NCs, making them a promising candidate for various applications in bioimaging, sensing, and light harvesting. Different kinds of ligands have been used in the past few years for nanocluster synthesis such as proteins, peptides, DNA, and small thiol molecules. However, the weak luminescence of most of the metal NCs compared to the conventional fluorophore and colloidal QDs has severely limited their use in many photonic applications. Ligands have played an important role in the PL properties by (i) a ligand–core interaction, (ii) a ligand–solvent interaction like solvent polarity and pH, and (iii) other interactions like ligand-coordination complex formation, metallophilic interaction, and many more. Various synthesis and post-synthesis strategies have been employed to improve the PL intensity of metal NCs. The tailoring of size, doping, structure, surface modification, and AIE are efficient methods to enhance the PL intensity of weakly luminescent metal NCs. ,,, It is reported that the PL of metal clusters originates from the core of the NCs and the surface organic ligand shell .…”
Section: Introductionmentioning
confidence: 99%
“…Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) has numerous applications in the taxonomic identification of microorganisms, 1 bacterial characterization 2 and tissue imaging, 3 synthetic polymer analysis, 4 and other fields 5 . Its popularity among non–mass spectrometrists stems largely from its speed, simplicity, ease of operation, and data analysis, which reduces the technical hurdles for individuals to utilize this technology for their research.…”
Section: Introductionmentioning
confidence: 99%